Protease-activated receptor 1-induced GABA release in cultured cortical astrocytes pretreated with GABA is mediated by the Bestrophin-1 channel - Lee, C. Justin; Yoon, Bo-Eun (TAYLOR & FRANCIS LTD, 2014)
gamma-amino butyric acid (GABA) is the main transmitter mediating inhibitory synaptic transmission in the brain and is released not only from a subset of neurons but also from astrocytes. It has been well established that GABA is released via Ca2+-dependent exocytosis of GABA-containing vesicles in neurons. However, a novel form of GABA release in astrocytes via the Ca2+-activated anion channel, Bestrophin-1 (Best1), has been recently reported. In here, we reveal a novel anion channel-mediated GABA release mechanism in cultured cortical astrocytes pretreated with GABA. We have observed that cultured cortical astrocytes do not contain much GABA. We demonstrate in these same astrocytes, pretreated with GABA, that activation of the protease-activated receptor 1 (PAR1) produces an increase in intracellular Ca2+ concentration that leads to opening of Best1 channels and the subsequent release of GABA. These results provide strong molecular evidence for a potential astrocyte-neuron interaction via PAR1-induced and Best1-mediated GABA release.
Keywords: LONG-TERM POTENTIATION; GLUTAMATE RELEASE; TONIC INHIBITION; DISEASE; GLIA; LOCALIZATION; NEURONS; MEMORY; CA1